Estrutura cerebral e estimativa do envelhecimento cerebral em indivíduos com deficiência congênita, isolada e não tratada do hormônio do crescimento - Gouy, Keila Ribeiro Villar (2024)
Introduction: Individuals with isolated GH deficiency (IGHD) due to a mutation in the GHRH receptor gene have a normal life expectancy and above 50 years of age, similar total cognitive performance, with better attention and executive function than controls. Objective: Evaluate their brain morphometry and brain aging using MRI. Methods: Thirteen IGHD and 14 controls matched by age, sex, and education, were enrolled. Quantitative volumetric data and cortical thickness were obtained by automatic segmentation using FreeSurfer software. The volume of each brain region was normalized by the intracranial volume. The Fazekas scale and the mesial temporal atrophy (MTA) score were also evaluated. The difference between the predicted brain age estimated by MRI using a trained neuronal network, and the chronological age, was obtained. p < 0.005 was considered significant and 0.005 < p < 0.05 as suggestive evidence of difference. Results: In IGHD, most absolute values of cortical thickness and regional brain volumes were similar to controls, but normalized volumes were greater in the white matter in the frontal pole and in the insula bilaterally, and in the gray matter, in the right insula and in left caudate (p < 0.005 for all comparisons) We also noticed suggestive evidence of a larger volume in IGHD in left thalamus (p = 0.006), right thalamus (p = 0.025), right caudate (p= 0.046) and right putamen (p = 0.013). Ten individuals in the IGHD group (77%) and 10 controls (71%) had Fazekas scale within the normal range and none of them showed changes in the MTA score. Predicted brain ages were similar between groups. Conclusion: IGHD is primarily associated with similar absolute brain measurements and a set of larger normalized volumes than controls. IGHD does not appear to alter the process of brain aging.